Feasibility of QKD over FSO Link - Husagić-Selman, Alma; Al-Khateeb, Wajdi Fawzi Mohammed; Saharudin, Shuhairi (2012)
Due to the advancements in the field of quantum computing and possible compromise of existing key-exchange algorithms, it is essential to explore performance and efficiency of new key-exchange techniques, such as Quantum Key Distribution (QKD). QKD is possible over fiber cable and Free Space Optical (FSO) links. Fiber based QKD may be used if direct line of sight link is not possible, but it brings along many problems related to material properties of fiber cable and detector limitations. It is therefore more convenient to use free-space based QKD whenever physically possible. Furthermore, FSO links can be satellite-supported in order to generate worldwide distribution of quantum keys. The FSO however greatly depends on weather conditions and link length, thus it is very important to evaluate these effects on the size of quantum key. In this paper, simulation-based evaluation of FSO QKD is done given tropical weather conditions specific for Malaysia. The paper discusses how different factors, such as link distance, weather, beam intensity and transceivers setup, influence key size when BB84 QKD protocol is used. For each weather condition specific for Malaysia key size was obtained, and the percentage of the received key compared to the total generated key is calculated. The results show the size of the final encryption key after being transmitted over FSO channel influenced by various weather conditions, which implies that it is possible to use FSO based QKD in Malaysia successfully.